Factors which delay surgery for undescended testis in Ontario: A retrospective population based cohort study on timing of orchidopexy between 2006 and 2012. Issue 5 (October 2022) - Dave, Sumit; Clark, Jordyn; Chan, Ernest P.; Richard, Lucie; Liu, Kuan; Wang, Peter (Zhantao); Shariff, Salimah; Welk, Blayne
Summary: Background: Delays in performing orchidopexy (OP) for undescended testis (UDT) result in loss of germ cells. Despite practice guidelines recommending OP by 18 months of age, significant delays in OP occur. This delay may impact fertility and increase the risk of testicular malignancy in boys with UDT. Objective: The objective of this study is to identify factors associated with delayed OP with the goal of identifying modifiable risk factors. Study design: A population-based, retrospective cohort study was conducted using linked databases held at ICES to evaluate factors associated with timing of OP in Ontario for 4339 male newborns undergoing their first OP between 2006 and 2012. Primary outcome was delayed OP (>18 months). Multivariable logistic regression analysis was performed to identify patient, physician, and hospital risk factors for delayed OP. Results: Median age at OP was 24 months, while median age at first surgical consult was 20 months (IQR 10–60 months). Older age at first surgical consult (>12 months vs. <9 months, OR 17.83) was identified as the primary risk factor for delayed OP, besides ICU hospitalization (OR 3.42), associated hypospadias (OR 2.30), higher hospital OP volume (OR 1.91), more healthcare visits in first year of life (OR 1.05), and older surgeon age (OR 1.02). Discussion: Our findings support reports that OP is often performed past guideline recommendations. Interventions that result in earlier referral for UDT (<6 months) may result in timely OP. Limitations for this study include potential misclassification or missing data within the utilized databases. Conclusion: The most important barrier to timely OP is delay in first surgical consultation. Aiming for an earlier referral through guideline modifications or education to referring providers may help achieve the goal of timely OP. Summary Table Logistic regression analysis of factors leading to delayed OP (>18 months) for UDT. Factors with odds ratio >1.0 associated with delayed OP. Summary Table Variables Reference Odds Ratio 95% CI p-value Patient factors Concurrent orchidectomy Yes/No 0.697 0.505–0.961 0.0278 ICU hospitalization (between 3 and 12 months) Yes/No 3.417 1.657–7.045 0.0009 Associated hypospadias Yes/No 2.300 1.593–3.321 <0.0001 Number of healthcare visits in first year of life 1-unit increase 1.054 1.038–1.071 <0.0001 Surgeon and hospital factors Surgeon main subspecialty Pediatric surgery vs. Urology 0.634 0.507–0.794 <0.0001 Surgeon age Per 1-year increase 1.022 1.011–1.032 <0.0001 Hospital volume Medium vs. Low 1.907 1.381–2.634 <0.0001 Consultation factors Age at consultation 9–12 months vs. <9 months 0.738 0.551–0.989 0.0416 >12 months vs. <9 months 17.828 14.482–21.947 <0.0001